Research progress of guidance and control technology for multi-UAVs cooperative attack - WANG Yujie; TANG Zhongnan; CHEN Qingyang; GAO Xianzhong; DENG Xiaolong (Hangkong gongcheng jinzhan, 2023)
The suicide UAV has the characteristics of long-term cruise and high-speed penetration, which can be used for target reconnaissance and attack. In order to give full play to the advantages of cluster attack, it is of great significance to break through the guidance and control technology for cooperative attack in complex environments. The basic ideas of exploring multi-UAVs cooperative control with spatio-temporal constraints are from single drone control to cluster dynamic coordination and single constraint to space-time comprehensive control. The application background of swarm attack is introduced, and the status of multi-UAVs coordinated strike system is analyzed. The key technologies such as impact time control guidance (ITCG), impact angle control guidance (IACG), and cluster cooperative control with spatio-temporal constraints are explored. The shortcomings of current UAV cooperative application are summarized, and the future research directions are prospected. The research of this paper has certain significance for the application of swarm attack operations and the design of multi-UAVs cooperative controllers.